Aplicações de resíduo de bauxita e cinza pesada da indústria do alumínio na fabricação de cimento Portland - Montini, Marcelo (Universidade Federal de São Carlos, 2009)
Presently, a sustainable development is considered fundamental for the success and competitivity company s. Believing in such, the major Brazilian aluminum manufactures have invested, over the last two years, more than U$S 50 millions on programs focused at sustainability. With this in mind, the aluminum industry is not saving efforts to find applications ecologically and economically feasible for its main waste. Thus, the target of the present research work was to investigate the possibility of adding red mud (in natura and calcinated) and bottom ash, solid wastes resulting from the aluminum production on Portland cement, as pozzolanic additive to the cement. Additionally, was evaluated the use of red mud on the raw meal for the production of Portland cement clinker. In order to study the pozzolanic properties (according to NBR 5752/92 e NBR 5751/92) from these wastes, tests on determination of the pozzolanic activity were carried out and one further step were prepared Portland cement samples with 6%, 14%, 30% and 50% of residue. Besides that, clinkers Portland cement were produced with 5.9 and 12% by sintering the raw meals at 1450oC. The results of the pozzolanic activity and physical and mechanical essays (setting time, expansibility and compressive strength) showed the addition of up to 46% of bottom ash did not affect negatively the quality of the produced cement. However, the red mud couldn t be considered a pozzolanic material because it has presented pozzolanic activity below the demanded limits from the Brazilian Cement Standards. The clinkers produced with red mud presented chemical and mineralogical characteristics similar to the clinker from a cement plant industry. In addition, the mortar (clinker from red mud + gypsum) presented a good compressive strength after 7 and 28 days of curing.
Application of red mud and bottom ash from aluminum production in the manufacture of Portland cement
Keywords: Cimento Portland; Rejeito de bauxita; Resíduos sólidos; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA